2009
DOI: 10.1111/j.1540-8159.2008.02298.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Conduction Disorders Following Percutaneous Aortic Valve Replacement

Abstract: We observed a higher incidence of early conduction disorders and need for PPM implantation after PAVR than generally reported after surgery. Whether this observation is clinically important requires larger prospective studies and follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
55
2
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 17 publications
8
55
2
1
Order By: Relevance
“…The evolution of conduction disorders took place over a period of 7 days after implantation. In our series, complete atrioventricular block was seen in 13.3%, while 8.9% suffered from type II second-degree atrioventricular block; thus, 22.2% of the patients developed an indication for permanent pacemaker implantation corroborating previous findings (27)(28)(29)(35)(36)(37)(38)(39). Their intracardiac measurements revealed that the occurrence of first-degree atrioventricular block was predominantly due to the prolongation of HV interval, which might be prognostically relevant (40).…”
Section: Conduction Disorderssupporting
confidence: 89%
See 2 more Smart Citations
“…The evolution of conduction disorders took place over a period of 7 days after implantation. In our series, complete atrioventricular block was seen in 13.3%, while 8.9% suffered from type II second-degree atrioventricular block; thus, 22.2% of the patients developed an indication for permanent pacemaker implantation corroborating previous findings (27)(28)(29)(35)(36)(37)(38)(39). Their intracardiac measurements revealed that the occurrence of first-degree atrioventricular block was predominantly due to the prolongation of HV interval, which might be prognostically relevant (40).…”
Section: Conduction Disorderssupporting
confidence: 89%
“…Among the electrocardiographic (ECG) criteria, right bundle branch block is the strongest predictor for pacemaker requirement (24,25). To date, some investigations have reported descriptive changes in the surface ECG after TAVI (15,(26)(27)(28)(29)(30)(31). In the published trials, the incidence of permanent pacemaker implantation after TAVI with the CoreValve system has been reported to be 20% to 42.5%, and that of a new left bundle branch block has been reported to range between 50% and 70% (5,(26)(27)(28)(29)(30)(31).…”
Section: Conduction Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Following TAVI, electrical conduction abnormalities are known to occur, [3][4][5][6][7][8][9][10][11][12][13][14][15][16] leading to the placement of a permanent pacemaker (PM) in 5-46% of cases [17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In this study, patients undergoing TAVI suffered a significant increase in atrio-ventricular (PQ interval) and intra-ventricular (QRS width) conduction times. Patients who were implanted with a CV prosthesis have the highest incidence of first-degree AVB and LBBB.…”
mentioning
confidence: 99%